Sport participation, physical activity and sedentary behavior in the transition from middle school to high school. Issue 4 (April 2020) - Shull, Emily R; Dowda, Marsha; Saunders, Ruth P.; McIver, Kerry; Pate, Russell R.
Abstract: Objectives: To examine associations between sport participation, and objectively assessed physical activity and sedentary behavior in youth during the transition from middle school to high school. Design: Longitudinal study with 2-year follow-up. Methods: Sport participation and accelerometer-measured physical activity and sedentary behavior were assessed in 306 children (122 males, 184 females) when they were in 7th and 9th grades (mean age of 12.5 ± 0.5 years). Results: Sport participation and physical activity declined from 7th to 9th grade, but total physical activity (d = 0.38, p < 0.0001) and moderate-to-vigorous physical activity (d = 0.26, p = 0.0004) remained higher in sport participants compared to non-participants. In 9th grade, the full sample of sport participants compared to non-participants had higher levels of total physical activity (20.7 min/h vs. 18.5 min/h) and moderate-to-vigorous physical activity (1.8 min/h vs. 1.6 min/h). Sex-specific analysis revealed similar patterns in both females and males. Sedentary behavior remained lower (d = -0.37, p = <0.0001) in the full sample of sport participants compared to non-participants (39.8 min/h vs. 41.7 min/h) in 9th grade. Similar patterns were observed in both females and males. Conclusions: Children's participation in sport is associated with greater levels of physical activity and lower levels of sedentary behavior during the transition from middle school to high school. Promoting children's participation in sports could be an effective public health strategy to help children meet the current physical activity guideline.